Using a 4D Virtual Reality Learning Environment to Follow the Evolution of an Engineering Project - Shallcross, D.; Dalvean, J.; Hadgraft, R.; Mann, K.; Sola, M.; Cameron, I.; Crosthwaite, C.; Maynard, Nicoleta; Tade, Moses; Kavanagh, J. (South African Society for Engineering Education (SASEE), 2011)
A new interactive learning environment that allows engineering students to follow the construction of a water treatment facility is described. The learning environment is built around the use of a series of spherical images compiled from high resolution photographs. Using intuitive controls the user can move from one spherical image node to another taken either at the same time but in a different location within the facility, or taken at the same location but at a different time. Between May 2010 and April 2011 sixteen complete photographic surveys of the water treatment facility owned by City West Water in Melbourne, Australia were collected. Each survey consisted of 26 viewed nodes with the exception of the final survey which contains 77 nodes. The water processing facility treats the effluent from a more conventional sewage treatment facility, producing recycled water of two grades – one for use as irrigation water and one as an industrial grade. The facility makes use of ultrafiltration and reverse osmosis processes to remove the contaminants including high salt levels from the effluent water. The interactive virtual reality learning environment constructed for the facility allows students to follow the construction through from the initial construction phase to final operation. The system allows students to work at their own pace, following facets that interest them. While photography is now complete the learning environment is currently under development and will be ready for use in the class room in 2012. This paper describes the learning environment as well as the intended learning outcomes.